К ВОПРОСУ О СОСТАВЕ И ПРОИСХОЖДЕНИИ МЕТЕОРОЛОГИЧЕСКОЙ ТЕРМИНОЛОГИИ - АНИСИМОВА, НАТАЛЬЯ (Studia Rossica Posnaniensia, 2006)
Features of meteorological terminology are considered in the article. Interaction of meteorological terms and common lexicon (adaptation of common lexicon by language of meteorology, its semantic transformation) is characterized. The most productive ways of forming the language of meteorology terms are described.